Large Midlatitude Stratospheric Temperature Variability Caused by Inertial Instability: A Potential Source of Bias for Gravity Wave Climatologies. Issue 19 (4th October 2018) - Rapp, M.; Dörnbrack, A.; Preusse, P.
Abstract: Stratospheric temperature perturbations (TP) that have previously been misinterpreted as due to gravity waves are revisited. The perturbations observed by radio occultations during December 2015 had peak‐to‐peak amplitudes of 10 K extending from the equator to midlatitudes. The vertically stacked and horizontally flat structures had a vertical wavelength of 12 km. The signs of the TP were 180 ∘ phase shifted between equatorial and midlatitudes at fixed altitude levels. High‐resolution operational analyses reveal that these shallow temperature structures were caused by inertial instability due to the large meridional shear of the polar night jet at its equatorward flank in combination with Rossby wave breaking. Large stratospheric TP owing to inertial instability do frequently occur in the Northern Hemisphere (Southern Hemisphere) from October to April (April to October) in the 39 years of ECMWF Re‐Analysis‐Interim data. During 10% of the days, TP exceed 5 K (peak to peak). Plain Language Summary: The stratosphere is the part of the atmosphere between altitudes of ∼15–50 km which contains the ozone layer that shields life from hazardous radiation. We use global stratospheric temperature measurements to learn about the variability of temperatures on vertical scales < 15 km. Usually, it is thought that such variations are caused by waves that are excited by the displacement of air when being lofted upward when, for example, the wind blows over mountains. The air then starts oscillating around its original height level because of gravity. Gravity waves are an important driver of stratospheric winds which, for example, determine the distribution of ozone. We present observations of large stratospheric temperature perturbations which could easily be misinterpreted as gravity waves. Combining the measurements with output of a numerical weather prediction model, we show that the observations are caused by a large‐scale atmospheric instability called inertial instability. Using meteorological data spanning the past 40 years, we quantify when and how often such temperature perturbations of a certain size occur. Our results are important for properly constructing gravity wave climatologies (where inertial instability events must be excluded)—which are in turn an important input for the correct formulation of climate models. Key Points: The spatial structure and temporal development of stratospheric inertial instability at 30‐45 degrees north is characterized with GPS radio occultation measurements in December 2015 The observed event is among the 0.1% strongest events in the ERA‐Interim climatology; moderate events occur during 10% of the time Inertial instability events are a possible source of bias for gravity wave climatologies constructed from temperature measurements